Pyrethroid resistance in a major African malaria vector Anopheles arabiensis from Mamfene, northern KwaZulu-Natal, South Africa - J. Mouatcho; G. Munhenga; K. Hargreaves; B. Brooke; M. Coetzee; L. Koekemoer (South African Journal of Science)
A population of Anopheles arabiensis, a major malaria vector in South Africa, was collected during 2005 from inside sprayed houses in Mamfene, northern KwaZulu-Natal, South Africa, using window exit traps. None of these specimens (n = 300 females) was found to be infected with Plasmodium falciparum. Insecticide susceptibility assays on 2 - 3 day old F1 progeny usingWHOsusceptibility kits revealed 100% susceptibility to bendiocarb, resistance to deltamethrin (95.91%) was suspected, while resistance to permethrin (78.05%) was confirmed. The knockdown resistant (kdr) genotype was not found in the surviving mosquitoes. Biochemical analysis using enzyme assays showed elevated levels of monooxygenase that correlated with the permethrin bioassay data. While elevated levels of non-specific esterase were found in some families (11/12 for Î±- and 6/12 for Î²-esterases), the data did not show any correlation with the permethrin bioassay. Analysis of permethrin and bendiocarb tolerant lines, selected in the laboratory to characterise biochemical resistance profiles, showed increased levels of non-specific esterase and monooxygenase activity in the case of the permethrin-selected cohorts, and elevated glutathione S-transferases and general esterases in that of the bendiocarb-selected line. Synergist assays, using piperonyl butoxide, confirmed the involvement of monooxygenase and glutathione S-transferase in pyrethroid and bendiocarb resistance. This study underlines the importance of routine surveillance for insecticide susceptibility in wild anopheline populations.